Connected body of metal material and method for

By using a film with thermoplastic resin as the main component at the cross-sectional junction of the metal material for melting and curing, problems such as long process time, poor repairability, and pollution problems when connecting metal materials in the prior art are solved, and a fast, strong repairability and non-pollution connection effect is achieved.

CN119630528APending Publication Date: 2025-03-14RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056739.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve rapid process time, strong repairability, no pollution of production lines and small changes in the thickness of the connecting part when connecting metal materials.

Method used

By confronting the cross-section of the flat metal material with the cross-section of other metal materials, and coating it in opposite parts with a film containing a thermoplastic resin as the main component, it is melted and solidified to achieve bonding.

Benefits of technology

A fast process time and strong repairability linking technology is achieved, which avoids contamination of the production line by bonding components, and the thickness of the linking part changes less.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630528A_ABST
    Figure CN119630528A_ABST
Patent Text Reader

Abstract

Provided is a connected body of a metal material in which a cross-section (A) of a flat metal material (A) and a cross-section (B) of a flat metal material (B) are brought into contact with each other, and at least a portion of the opposing portion is covered with a film containing a layer mainly composed of a thermoplastic resin. The metal material A and the metal material B are connected to form a metal material connecting body, the facing portion is a region spanning both an end edge portion A of the metal material A and an end edge portion B of the metal material B, and the film is a film melted and solidified at the facing portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal material connection body formed by butting and connecting a cross section of a metal material with a cross section of another metal material, and a metal material connection method suitable for butting and connecting a cross section of a metal material with a cross section of another metal material.

[0002] In this specification, the term "edge portion" refers to a planar portion of at least one of the front surface and the back surface near the end of a metal material to be connected.

[0003] In this specification, the "opposing portion" refers to a region spanning the above-mentioned "edge portion", and refers to a region of two planar portions, namely, a planar portion on the front side and a planar portion on the back side of the metal material.

[0004] In this specification, “cross section” is not limited to a cut surface, and “butting a cross section of a metal material against a cross section of another metal material” also includes butting ends or beginnings of metal materials that do not have a cut surface due to cutting.

[0005] In this specification, "butting" means facing each other, and is not limited to facing each other with the entire surfaces in contact. Background Art

[0006] In a roll-to-roll manufacturing device that conveys metal plates and / or metal foils (hereinafter referred to as coils) that are wound into rolls and continuously processed, in order to operate continuously, when the wound portion of the coil becomes less or at the interrupted portion of the coil, it is necessary to join the old coil being continuously processed with the new coil.

[0007] As a technology for connecting the starting end of a strip of metal material to the end of another strip of metal material, the following joining method has been disclosed, namely, a pad is arranged on the back side of a butt joint formed by butting the end portions together, and an arc welding torch is moved from the front side of the butt joint to weld the butt joint (Patent Document 1).

[0008] However, the technology of Patent Document 1 relates to a connection based on welding, and after connection, it cannot be disassembled without being destroyed. Therefore, there is a problem that a reconnection operation (hereinafter also referred to as repair) cannot be easily performed for a fault such as a misalignment of the connection part.

[0009] As connection means other than welding, connection using a liquid adhesive, connection using a film-like thermosetting adhesive (hereinafter referred to as a thermosetting adhesive film), connection using an adhesive tape, connection by caulking, etc. can be considered, but each has the following problems.

[0010] In the connection using a liquid adhesive, a coating process of applying a liquid thermosetting resin composition and a curing process of allowing the resin composition to undergo a polymerization reaction to solidify it after coating are required. In the coating process, the coating of the resin composition takes time, and in the curing process, the polymerization reaction takes time. Thus, in the connection based on a liquid adhesive, the process time involved in the connection becomes longer, so there is a problem of lack of convenience. In addition, in the case of a liquid thermosetting adhesive, it is impossible to repair or difficult to repair.

[0011] When bonding is performed using a thermosetting adhesive film, a coating step is not required and the process time can be shortened, but repair is not possible after bonding.

[0012] When the thermosetting adhesive film is a B-stage film, polymerization reaction easily proceeds at room temperature, so the storage stability is poor and it cannot be stored for a long time at room temperature. That is, when the thermosetting adhesive film is a B-stage film, it needs to be stored at low temperature and requires a low-temperature storage warehouse, so it is difficult to store a large amount for a long time, which lacks convenience.

[0013] In the connection using adhesive tape, there is a problem that the base resin, tackifier and other adhesive components (hereinafter referred to as adhesive) of the resin composition constituting the adhesive layer of the adhesive tape adhere to the conveying path and mold of the production line and contaminate the conveying path and mold. In addition, when the adhesive tape is peeled off due to an accident, the adhesive layer of the peeled adhesive tape is exposed, and the adhesive may also contaminate the conveying path and mold.

[0014] In the connection based on caulking, metal materials are overlapped for caulking, and protrusions are generated due to the caulking. Therefore, the thickness of the caulking part as the connection part increases, which makes it difficult to apply to low production lines. In addition, for caulking, a space for metal materials that is larger than the caulking diameter and flat is required, and there is a problem that sufficient connection strength cannot be obtained for metal materials with complex shapes and narrow spacing. In addition, when passing through multiple liquid medicine tanks, more liquid medicine is carried into the next tank, the contamination of the liquid medicine is aggravated, and there is a problem that the life of the liquid medicine is shortened.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent Document 1: Japanese Patent Application Publication No. 2012-61511 Summary of the invention

[0018] Problems to be solved by the invention

[0019] The present invention is completed in view of the above technical background, and its purpose is to provide a connection technology that can be repaired, has a short process time, does not worry about adhesive components causing contamination to the production line, and has little thickness variation at the connection site.

[0020] In order to achieve the above-mentioned object, the present invention provides the following means.

[0021] <Metallic material connection body>

[0022] [1] A connection body of metal materials, which is formed by butting a cross-section A of a flat metal material A with a cross-section B of a flat metal material B, and connecting the metal material A and the metal material B by covering at least a portion of the facing portions with a film containing a layer mainly composed of a thermoplastic resin, wherein the facing portions are regions spanning both an end edge portion A of the metal material A and an end edge portion B of the metal material B, wherein the film is a film that has been melted and solidified at the facing portions.

[0023] [2] The connected body of metal materials according to [1], wherein the metal material A and the metal material B are at least one selected from a metal plate having a thickness of 1 mm or less and a metal foil having a thickness of 1 mm or less.

[0024] [3] The connection body of metal materials according to [1] or [2], wherein the metal material A and the metal material B are in the form of strips, and the metal material A and the metal material B are butted together so as to be continuous in the length direction.

[0025] [4] The connected body of metal materials according to any one of [1] to [3], wherein the metal material A and the metal material B are coils formed by winding at least one selected from a metal plate and a metal foil into a coil.

[0026] [5] A connection body of metal materials according to any one of [1] to [4], which is formed by coating two planar portions, namely, a planar portion on the front side of the metal material A and the metal material B, and a planar portion on the back side of the metal material A and the metal material B.

[0027] [6] The connection body of metal materials according to any one of [1] to [5], wherein the thermoplastic resin is an amorphous thermoplastic resin.

[0028] [7] The metal material connection body according to [6], wherein the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resins and phenoxy resins.

[0029] [8] The metal material connection body according to [7], wherein the amorphous thermoplastic resin is an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, or an amorphous thermoplastic resin not containing an epoxy group.

[0030] [9] The metal material connection body according to any one of [1] to [8], wherein the thickness of the film is 10 μm to 3 mm.

[0031]

[10] The metal material connection body according to any one of [1] to [9], wherein the film has an adhesive on the surface covering the opposing portion, and the adhesive has a function of temporarily fixing the film and does not have a bonding function.

[0032] <Method of joining metal materials>

[0033]

[11] A method for connecting metal materials, wherein a cross-section A of a flat metal material A is butted against a cross-section B of a flat metal material B, at least a portion of the facing areas spanning the end edge A of the metal material A and the end edge B of the metal material B is coated with a film comprising a layer mainly composed of a thermoplastic resin, and the film is melted and solidified to connect the metal material A to the metal material B.

[0034]

[12] The method for connecting metal materials according to

[11] , wherein the metal material A and the metal material B are at least one selected from a metal plate having a thickness of 1 mm or less and a metal foil having a thickness of 1 mm or less.

[0035]

[13] According to the method for connecting metal materials described in

[11] or

[12] , the metal material A and the metal material B are in the form of strips, and the metal material A and the metal material B are butt-jointed in a continuous manner in the length direction.

[0036]

[14] The method for connecting metal materials according to any one of

[11] to

[13] , wherein the metal material A and the metal material B are coils formed by winding at least one selected from a metal plate and a metal foil into a coil.

[0037]

[15] A method for connecting metal materials according to any one of

[11] to

[14] , wherein the coating is performed on the planar portions on the front side of the metal material A and the metal material B, and on the planar portions on the back side of the metal material A and the metal material B.

[0038]

[16] The method for connecting metal materials according to any one of

[11] to

[15] , wherein the thermoplastic resin is an amorphous thermoplastic resin.

[0039]

[17] The method for joining metal materials according to

[16] , wherein the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resins and phenoxy resins.

[0040]

[18] The method for joining metal materials according to

[17] , wherein the amorphous thermoplastic resin is an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, or an amorphous thermoplastic resin not containing an epoxy group.

[0041]

[19] The method for connecting metal materials according to any one of

[11] to

[18] , wherein the thickness of the film is 10 μm to 3 mm.

[0042]

[20] According to any one of

[11] to

[19] , the film has an adhesive on the surface covering the opposing portion, and the adhesive has a function of temporarily fixing the film and does not have a bonding function.

[0043] Effects of the Invention

[0044] It is possible to provide a joining technology that has a short process time, is repairable, has a short process time, does not worry about the adhesive component contaminating the production line, and has little thickness variation at the joining part. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a plan view of a metal material connection body in one embodiment of the present invention, and is a schematic diagram of a connection body obtained by butting and connecting the cross sections in the width direction of a flat plate-shaped metal material A and a flat plate-shaped metal material B, both of which are strip-shaped.

[0046] Figure 2 It is a front view of a metal material connection body in one embodiment of the present invention, and is a schematic diagram of a connection body obtained by butting and connecting the cross sections in the width direction of a flat plate-shaped metal material A and a flat plate-shaped metal material B, both of which are strip-shaped.

[0047] Figure 3 It is a front view of a connection body of metal materials in another embodiment of the present invention, and is a schematic diagram of a connection body in which a flat plate-shaped metal material A and a flat plate-shaped metal material B are both in a strip shape and their width direction cross sections are butted and joined. DETAILED DESCRIPTION

[0048] Hereinafter, embodiments of the present invention will be described in detail.

[0049] In this specification, connection refers to connecting objects to form a continuum, and joining is a subordinate concept. In this specification, joining refers to connecting objects in a contacting manner, and bonding and welding are subordinate concepts. Bonding refers to the process of forming a bonded state between two bonded materials (objects to be bonded) through an organic material (thermosetting resin, thermoplastic resin, etc.) such as a tape or adhesive. Welding refers to the process of melting the surface of a thermoplastic resin or the like by heat and cooling it, thereby generating entanglement based on molecular diffusion to form a bonded state.

[0050] [Metallic material connection body]

[0051] The connection body of metal materials of the present invention is a connection body of metal materials formed by connecting the cross section A(5) of a flat metal material A(1) with the cross section B(6) of a flat metal material B(2), and covering at least a portion of the area spanning the end edge A(7) of the above-mentioned metal material A(1) and the end edge B(8) of the above-mentioned metal material B(2), i.e., the facing portion (9), with a film (3) comprising a layer mainly composed of a thermoplastic resin, and the above-mentioned metal material A and the above-mentioned metal material B are connected. The above-mentioned film (3) is a film that has been melted and solidified at the above-mentioned facing portion (9).

[0052] In this specification, "main component" refers to the component with the highest content among the resin components in the film. The film preferably contains 50% by mass or more of the resin component, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0053] By melting and solidifying the film (3) at the opposing positions (9), the film (3) is joined to the end edge A (7) of the metal material A (1), and the film (3) is joined to the end edge B (8) of the metal material B (2), thereby connecting the metal material A to the metal material B, and obtaining a connection body showing excellent connection strength.

[0054] The molten film (3) at the opposing portion (9) enters the gap between the section A (5) of the metal material A (1) and the section B (6) of the metal material B (2) and solidifies, whereby the connection formed by joining the butt surfaces (4) of the section A (5) and the section B (6) shows a better connection strength. However, in the connection of the present invention, a gap may also exist between the section A (5) and the section B (6).

[0055] The bonding strength is affected by factors such as the thickness of the film, the molecular weight of the polymer constituting the film, the chemical structure, the mechanical properties, and the viscoelastic properties, in addition to the strength of the interfacial interaction between the above-mentioned film and the metal material. Therefore, although the details of the mechanism by which the bonded body of the present invention exhibits excellent bonding strength are not yet clear, it is presumed that the main reason is the formation of chemical bonds such as hydrogen bonds and intermolecular forces such as van der Waals forces at the interfaces between the film and the metal material A and the film and the metal material B. However, in the above-mentioned bonded body, the state or characteristics of the interface between the film and the metal material are determined by analyzing the chemical structure of the extremely thin interface below the nanometer level. Therefore, at the current level of technology, it is impossible or impractical to express such a difference by determining it in a strict numerical range.

[0056] At present, it is difficult to strictly distinguish between a connection body connected by a film (3) that has been melted and solidified at the opposing parts (9) and a connection body connected by an adhesive tape through analysis and other means. In the current technology, this is difficult as mentioned above, but in practice, as described below, such a connection body can be distinguished by whether there is a roundness angle at the corner of the film, whether there is a thickness deviation, and the surface properties of the film surface in contact with the end edge.

[0057] The film before melting and solidification has a sharp cut surface formed in the manufacturing process of the film, but the film (3) constituting the connecting body of the metal material of the present invention is a film (3) that has been melted and solidified at the opposing parts (9), so it is presumed that it does not have a sharp cut surface formed in the manufacturing process of the film, and the corners of the film are rounded.

[0058] Films are usually manufactured in a manner to form a uniform thickness, so no thickness deviation is observed in the film before melting and solidification. However, the film (3) constituting the metal material connection body of the present invention is a film (3) that has been melted and solidified at the opposing portion 9, so it is presumed that there is a thickness deviation that is inevitably generated during the melting and solidification process. As a method for measuring thickness deviation, any appropriate method such as measuring the thickness of any multiple points within the surface of the object to be measured and performing statistical processing can be used. As a method for measuring such thickness, there can be listed methods such as micrometers, micro calipers, micrometer indicators, etc. that are accompanied by physical contact; non-contact methods that measure the transmittance and reflectance of α rays, X-rays, infrared rays, electromagnetic waves, etc. on the object to be measured; methods that cut the object to be measured at any measurement location and observe it with an optical microscope or an electron microscope; etc., and combinations thereof can also be used.

[0059] It is speculated that the film (3) that has been melted and solidified at the facing portion (9) has the surface properties of the edge portion A (7) transferred to the film surface in contact with the edge portion A (7), and the surface properties of the edge portion B (8) transferred to the film surface in contact with the edge portion B (8). Here, the surface properties refer to fine irregularities produced on the surface of the metal material during the process of machining the metal material, etc.

[0060] The connection of the present invention is a connection that utilizes the phase change (solid-liquid-solid) of the film with thermoplastic resin as the main component, and is a connection that is not accompanied by chemical reactions such as polymerization reactions. Since it is used in a state after the polymerization reaction is completed, the polymerization reaction will not occur even at room temperature, and it can be stored for a long time at room temperature. The above-mentioned film can be softened and melted by heat, and can be easily peeled off, so it has excellent disassembly. In addition, since the film with thermoplastic resin as the main component has the property of thermoplasticity, it can be softened, melted and solidified reversibly and repeatedly, and the repairability is also excellent. The connection using the film with thermoplastic resin as the main component utilizes the phase change (solid-liquid-solid) of the film, and has the advantages of being completed in a short time and short process time compared to the polymerization reaction accompanied by the formation of chemical bonds. In addition, the thermoplastic resin is not a liquid at room temperature but a solid after the polymerization reaction is completed. It is bonded by a mechanism different from adhesion, so there is no need to use an adhesive for bonding purposes, and there is no need to worry about production line contamination caused by the adhesive. In addition, since the polymerization reaction has been completed, the heat resistance and chemical resistance are also excellent. In addition, since the connection is made using a thin film, there is an advantage that the thickness variation at the connection portion is less compared to caulking or the like.

[0061] Figure 1 to Figure 3 This is a schematic diagram of a connected body in which a flat plate-shaped metal material A (1) and a flat plate-shaped metal material B (2) are both in a strip shape and their cross sections in the width direction are butted and joined.

[0062] The above membranes, such as Figure 2 As shown, it is preferred that the metal material A (1) and the metal material B (2) are covered on at least one of the planar portions on the front side of the metal material A and the metal material B, and the planar portions on the back side of the metal material A and the metal material B, which are the facing portions (9).

[0063] like Figure 3 As shown, it is particularly preferred that the metal material A (1) and the metal material B (2) are coated on two planar portions, namely, the planar portion on the front side of the metal material A and the metal material B, and the planar portion on the back side of the metal material A and the metal material B, which are the facing portions (9).

[0064] <Metal Materials>

[0065] The shapes of the metal material A and the metal material are not particularly limited as long as they are flat plates, but the present invention is suitable for connecting metal plates with a thickness of 1 mm or less or metal foils with a thickness of 1 mm or less, and is suitable for connecting opposing portions of the metal material A and the metal material B in a strip (long strip) shape so as to be continuous in the length direction. Specifically, it is suitable for connecting roll materials formed by winding metal foil into a roll shape, and is particularly suitable for connecting the end of a preceding roll material fed into a production line with the beginning of a subsequent roll material, and for connecting the end with the beginning when there is a break in the roll material.

[0066] In this specification, the metal foil refers to a foil formed by stretching a highly ductile metal into a thin paper shape.

[0067] There is no particular restriction on the type of metal of metal material A and metal material B, and it is preferably at least one selected from aluminum, iron, copper, magnesium and their alloys. From the perspective of the strength of the interfacial adhesion with the above-mentioned film, if it is at least one selected from aluminum alloy and iron alloy, a strong connection can be achieved, so it is particularly preferred.

[0068] In addition, the surface of the metal material A or the metal material B may be subjected to metal plating treatment, or may be coated with a resin.

[0069] By pre-treating the opposing portions of the metal material A and the metal material B covered by the film, high adhesion may be obtained between the film and the metal material. As the pre-treatment, it is preferred to clean the surface of the metal material or to give the surface a concave-convex treatment. When the metal material is composed of aluminum or iron, it is preferred to perform at least one pre-treatment selected from degreasing treatment, UV ozone treatment, sandblasting treatment, grinding treatment, plasma treatment and etching treatment.

[0070] Only one type of pretreatment may be performed, or two or more types may be performed. As specific methods of these pretreatments, known methods can be used.

[0071] <Film>

[0072] In the present specification, the film refers to a film obtained by forming a resin mainly composed of a thermoplastic resin into a thin film or a film obtained by forming a resin composition mainly composed of a thermoplastic resin into a thin film.

[0073] From the perspective of fully imparting the properties of the thermoplastic resin to the film, the content of the thermoplastic resin is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and most preferably 90% by mass or more in the resin component in the film.

[0074] The thermoplastic resin is preferably an amorphous thermoplastic resin. The amorphous thermoplastic resin in the present embodiment refers to a resin having no crystals or a very small amount of crystals, and specifically, a crystal having a heat of fusion of 15 J / g or less.

[0075] The heat of fusion is calculated from the area of ​​the endothermic peak of DSC (differential scanning calorimeter) and the weight of the thermoplastic resin component. When the film contains an inorganic filler, etc., it is calculated from the weight of the thermoplastic resin component excluding the inorganic filler. Specifically, 2-10 mg of the sample can be weighed, placed in an aluminum pan, and heated from 23°C to 200°C or above at 10°C / min using DSC (DSC8231 manufactured by Rigaku Co., Ltd.) to obtain a DSC curve, and then calculated from the area of ​​the endothermic peak during melting obtained from the DSC curve and the weighed value.

[0076] The heat of fusion of the amorphous thermoplastic resin is more preferably 11 J / g or less, further preferably 7 J / g or less, and further preferably 4 J / g or less, and the melting peak is most preferably below the detection limit.

[0077] The film mainly composed of an amorphous thermoplastic resin with a melting heat of 15 J / g or less does not experience a sharp drop in viscosity as seen in conventional hot melt adhesives when heated for melting, and does not reach a low viscosity (0.001 to 100 Pa·s) state even in a high temperature range exceeding 200°C. Therefore, the film does not melt and flow out, and the thickness after solidification can be maintained within a specified range, and a high bonding strength can be stably obtained.

[0078] When the amorphous thermoplastic resin as the main component of the film contains a small amount of crystals, the melting point is preferably 50 to 400° C., more preferably 60 to 350° C., and further preferably 70 to 300° C. By setting the melting point within the range of 50 to 400° C., the film is efficiently deformed and melted by heating, and the film is effectively wetted and spread on the bonding surfaces between the film and the metal material A and between the film and the metal material B, thereby obtaining a high bonding strength.

[0079] In this specification, the melting point of a thermoplastic resin refers to the melting peak temperature measured by DSC. It should be noted that when a melting peak cannot be obtained and the heat of fusion is 15 J / g or less, the temperature obtained by adding 70°C to the glass transition temperature is used as the melting point. The glass transition temperature refers to the temperature at which the DSC curve of the second cycle of heating to 200°C, cooling to 40°C or less, and then heating to 200°C begins to decrease by DSC.

[0080] The amorphous thermoplastic resin is preferably at least one selected from thermoplastic epoxy resins and phenoxy resins. Thermoplastic epoxy resins and phenoxy resins have low cohesive forces within the resins, so they interact strongly with metal materials and can connect metal materials with a higher bonding force than conventional crystalline hot melt adhesives. In addition, thermoplastic epoxy resins and phenoxy resins have excellent flexibility and toughness, so high-strength bonding can be obtained.

[0081] The amorphous thermoplastic resin is preferably an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more or containing no epoxy group.

[0082] The epoxy equivalent (the weight of the thermoplastic resin containing 1 mol of epoxy groups) is the value of the epoxy equivalent of the thermoplastic resin contained in the film before bonding, and is a value measured by the method specified in JIS-K7236:2001 (unit: "g / eq."). Specifically, a potentiometric titration apparatus is used, tetraethylammonium bromide acetic acid solution is added, and a 0.1 mol / L perchloric acid-acetic acid solution is used. The solvent-diluted product (resin varnish) is a value obtained by calculating the solid conversion value from the non-volatile component. It should be noted that in the case of a mixture of two or more resins, it can also be calculated from the respective contents and epoxy equivalents.

[0083] The epoxy equivalent of the amorphous thermoplastic resin is more preferably 2,000 or more, further preferably 5,000 or more, and further preferably 9,000 or more, and most preferably it is above the detection limit and substantially no epoxy group is detected. It should be noted that the epoxy equivalent being above the detection limit means that no epoxy group is detected when the epoxy equivalent is measured based on JIS K 7236:2001 described below.

[0084] By using a film mainly composed of an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, a rapid decrease in viscosity can be more effectively suppressed, and a higher bonding strength can be stably obtained.

[0085] 《Thermoplastic Epoxy Resin》

[0086] The thermoplastic epoxy resin is preferably a polymer of (a) a bifunctional epoxy resin monomer or oligomer and (b) a bifunctional compound having two identical or different functional groups selected from phenolic hydroxyl groups, carboxyl groups, mercapto groups, isocyanate groups and cyanate groups.

[0087] By using this compound, the polymerization reaction to form a linear polymer proceeds preferentially, and a thermoplastic epoxy resin having desired properties can be obtained.

[0088] The (a) bifunctional epoxy resin monomer or oligomer refers to an epoxy resin monomer or oligomer having two epoxy groups in the molecule.

[0089] Specific examples of the above (a) include, for example, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bifunctional phenol novolac type epoxy resins, bisphenol AD ​​type epoxy resins, biphenyl type epoxy resins, bifunctional naphthalene type epoxy resins, bifunctional alicyclic epoxy resins, bifunctional glycidyl ester type epoxy resins (e.g., diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl dimer acid diglycidyl ester, etc.), bifunctional glycidyl amine type epoxy resins (e.g., diglycidyl aniline, diglycidyl toluidine, etc.), bifunctional heterocyclic epoxy resins, bifunctional diaryl sulfone type epoxy resins, hydroquinone type epoxy resins (e.g., hydroquinone diglycidyl ether, 2,5-ditert-butyl ether, etc.), butylhydroquinone diglycidyl ether, resorcinol diglycidyl ether, etc.), bifunctional alkylene glycidyl ether compounds (e.g., butanediol diglycidyl ether, butenediol diglycidyl ether, butynediol diglycidyl ether, etc.), bifunctional glycidyl group-containing hydantoin compounds (e.g., 1,3-diglycidyl-5,5-dialkylhydantoin, 1-glycidyl-3-(glycidyloxyalkyl)-5,5-dialkylhydantoin, etc.), bifunctional glycidyl group-containing siloxanes (e.g., 1,3-bis(3-glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane, α,β-bis(3-glycidyloxypropyl)polydimethylsiloxane, etc.), and modified products thereof. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and biphenyl type epoxy resin are preferred from the viewpoint of reactivity and operability.

[0090] Examples of the bifunctional compound having a phenolic hydroxyl group of (b) include mononuclear aromatic dihydroxy compounds having one benzene ring such as catechol, resorcinol, and hydroquinone, bisphenols such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), and bis(4-hydroxyphenyl)ethane (bisphenol AD), compounds having a condensed ring such as dihydroxynaphthalene, bifunctional phenol compounds into which an allyl group is introduced such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.

[0091] Specific examples of the carboxyl group-containing compound (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0092] Examples of the bifunctional compound having a mercapto group (b) include ethylene glycol bismercaptoacetate and ethylene glycol bismercaptopropionate.

[0093] Specific examples of the isocyanate group-containing bifunctional compound (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMD), and toluene diisocyanate (TDI).

[0094] Specific examples of the cyanate group-containing bifunctional compound (b) include 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)ethane, and bis(4-cyanophenyl)methane.

[0095] In the above (b), from the perspective of obtaining a thermoplastic polymer, a bifunctional compound having a phenolic hydroxyl group is preferred. From the perspective of heat resistance and connectivity, a bifunctional compound having two phenolic hydroxyl groups and a bisphenol structure or a biphenyl structure is preferred. From the perspective of heat resistance and cost, at least one selected from bisphenol A, bisphenol F and bisphenol S is preferred.

[0096] When the above-mentioned (a) is a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a bisphenol S type epoxy resin, or a biphenyl type epoxy resin, and the above-mentioned (b) is at least one selected from bisphenol A, bisphenol F, and bisphenol S, the polymer obtained by polymerization of the above-mentioned (a) and (b) has a structure in which a p-phenylene structure and an ether bond are the main skeleton, a main chain formed by connecting them with an alkylene group, and hydroxyl groups generated by addition polymerization are arranged on the side chains.

[0097] The mechanical strength of the polymer after polymerization can be improved by the linear structure composed of the p-phenylene skeleton, and the adhesion to metal materials can be improved by the hydroxyl group arranged in the side chain. As a result, high connection strength can be achieved while maintaining the adhesiveness of the thermosetting resin. Furthermore, in the case of a thermoplastic resin, it can be recycled and repaired by softening and melting it with heat, which can improve the recyclability and repairability that are the problems of thermosetting resins.

[0098] 《Phenoxy resin》

[0099] Phenoxy resin is a polyhydroxy polyether synthesized from bisphenols and epichlorohydrin, and has thermoplasticity. In the manufacture of phenoxy resin, there are known methods of utilizing the direct reaction of dihydric phenols with epichlorohydrin, and methods of utilizing the addition polymerization of diglycidyl ethers of dihydric phenols with dihydric phenols, and the phenoxy resin used in the present invention can be obtained by any preparation method. In the case of the direct reaction of dihydric phenols with epichlorohydrin, as dihydric phenols, for example, phenols such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenylene glycol, and diphenylfluorene can be listed; aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol. Among them, bisphenol A, bisphenol F, and bisphenol S are preferred from the aspects of cost, connectivity, viscosity, and heat resistance. They can be used alone or in combination of two or more.

[0100] The phenoxy resin has a chemical structure similar to that of the epoxy resin, and has a main skeleton composed of a p-phenylene structure and an ether bond, a main chain formed by connecting these, and a structure in which hydroxyl groups are arranged in side chains.

[0101] 《Physical Properties of Thermoplastic Epoxy Resins and Phenoxy Resins》

[0102] The above-mentioned thermoplastic epoxy resin and phenoxy resin, the polystyrene conversion value obtained by GPC (gel permeation chromatography) is preferably 10,000 to 500,000, more preferably 18,000 to 300,000, and further preferably 20,000 to 200,000. The weight average molecular weight is calculated by the elution peak position detected by GPC, and is the value of the molecular weight converted to standard polystyrene. When the weight average molecular weight is a value in this range, the balance between thermoplasticity and heat resistance is good, and a connected body can be efficiently obtained by melting, and its heat resistance also becomes higher. If the weight average molecular weight is 10,000 or more, the heat resistance is excellent. If the weight average molecular weight is 500,000 or less, the viscosity during melting is low and the connectivity becomes high.

[0103] 《Components other than resin components in the film》

[0104] If necessary, the film may contain fillers and additives as components other than the resin component, or may not contain them within a range not hindering the purpose of the present invention.

[0105] Examples of the filler include inorganic fillers and organic fillers (resin powders).

[0106] Examples of the inorganic filler include spherical fused silica, metal powders such as iron, silica sand, talc, calcium carbonate, mica, acid clay, diatomaceous earth, kaolin, quartz, titanium oxide, silicon dioxide, phenolic resin microspheres, and glass spheres.

[0107] When the film contains fillers, the content of the fillers in the total volume 100% by volume of the film is preferably 50% by volume or less, more preferably 30% by volume or less, further preferably 20% by volume or less, and most preferably 10% by volume or less. It should be noted that the volume of the fillers can be obtained by dividing the weight of the fillers contained in the film by the apparent density of the fillers.

[0108] The content of the resin component in the total volume 100% by volume of the film is preferably 10% by volume or more, more preferably 20% by volume or more, further preferably 30% by volume or more, further preferably 50% by volume or more, in one embodiment 80% by volume or more, in another embodiment 90% by volume or more, and in yet another embodiment 99% by volume or more.

[0109] Examples of the additives include defoaming agents, coupling agents such as silane coupling agents, and pigments, and these may be contained alone or in combination of two or more.

[0110] The content of the additive in the film is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less.

[0111] The content of the resin component in the film is preferably 10 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, further preferably 50 mass % or more, in one embodiment 80 mass % or more, in another embodiment 90 mass % or more, and in yet another embodiment 99 mass % or more.

[0112] 《Morphology and physical properties of membranes》

[0113] The thickness of the film is preferably 10 μm to 3 mm.

[0114] From the perspective of obtaining a connected body with excellent connectivity in a short process time, the thickness of the film is more preferably 1 mm or less, further preferably 0.5 mm or less, further preferably 0.3 mm or less, particularly preferably 0.2 mm or less, and most preferably 0.1 mm or less.

[0115] By setting the film thickness to 10 μm to 3 mm, the film can be efficiently expanded at the bonding surfaces between the film and the metal material A and between the film and the metal material B by heating, pressing, etc., thereby obtaining a high bonding strength.

[0116] The film may be a single layer or a laminate comprising multiple layers. From the perspective of ease of manufacture and improved bonding strength, the layer of the thermoplastic resin is preferably a single layer. Alternatively, it may be a multilayer formed by laminating the thermoplastic resin on a film substrate composed of a resin having a higher melting point than the above-mentioned resin composition. In such a case, when the metal substrate is heated and welded, the resin film substrate does not melt and the thickness of the resin film substrate remains, so that a good bonding strength can be maintained.

[0117] In addition, the film may have adhesiveness within a range that does not hinder the bonding force and the heat resistance thereof.

[0118] To impart tackiness, a tackifier may be mixed into the thermoplastic resin, or an adhesive may be applied to the film. Preferably, the adhesive serves to temporarily fix the film and does not serve as an adhesive. The adhesive that serves to temporarily fix the film and does not serve as an adhesive is, for example, an adhesive that is retained within the film surface and covers the surface of the opposing portion (9) without being exposed to the outside of the surface.

[0119] The adhesive may be applied to the entire surface of the facing portion (9), or may be applied to a portion of the surface of the facing portion (9) in the form of stripes, dots, grids, tiles (a shape in which a plurality of quadrilaterals are arranged with gaps), etc. The smaller the coating area, the lower the viscosity, but a smaller coating area can reduce the risk of the adhesive being exposed from the end surface of the film after connection to the outside and becoming a major cause of contamination.

[0120] In conventional adhesive tapes, the bonding force between the metal material and the film is borne only by the adhesiveness of the adhesive layer of the adhesive tape, but in the case of the above-mentioned thermoplastic film, the bonding force is borne by the bonding based on the melting and solidification of the thermoplastic resin as described above, so the adhesiveness is preferably such that the above-mentioned temporary fixing function is exerted. That is, when the above-mentioned film is placed on the metal material, the above-mentioned film does not need to be attached to the metal material as long as the resistance becomes large (becomes difficult to slide) when a shearing force is applied.

[0121] When the purpose is to impart enough tack to achieve a temporary fixing function, the amount of the adhesive applied is preferably kept to a minimum that allows for temporary pressing (anti-slip) of the film.

[0122] In conventional adhesive tapes, for adhesive tapes having an adhesive layer only on one side, after being joined to a metal material, the adhesive layer is basically not exposed on the outside of the joining surface. However, if there is a portion where the adhesive layer is exposed at the end of the joining surface, the adhesive may adhere to the conveying path and mold of the production line, sometimes causing contamination.

[0123] In addition, the end faces of strip-shaped metal materials are not necessarily limited to straight lines. In such a case, a gap is generated between the end faces of the two connected pieces of metal materials. When an adhesive tape is pasted in the gap, the adhesive layer is exposed from the gap, and the adhesive will adhere to the conveying path and mold of the production line, sometimes causing contamination.

[0124] Furthermore, when the single-sided adhesive tape is superimposed on the substrate, the exposure of the adhesive portion becomes less, but it is difficult to make the back and front sides completely consistent. In addition, when butt-jointed, the shape of the end face sometimes becomes irregular, so the adhesive layer of this part is exposed, and the adhesive may adhere to the conveying path and mold of the production line, sometimes causing contamination.

[0125] According to the present invention, in which the bonding force is borne by bonding based on melting and solidification of a thermoplastic resin, there is basically no need for an adhesive for bonding purposes, and when an adhesive is used for purposes such as positioning, its use can be minimized, thereby avoiding all the above-mentioned problems associated with conventional adhesive tapes.

[0126] The breaking strength of the film in the bonded body of the metal material A and the metal material B connected by the film is preferably 20 to 1000 N / 25 mm. In the case where the bonded body is made of two films on the front and back, the strength is the strength when the film is first broken.

[0127] The breaking strength of the film in the above-mentioned connected body is more preferably 50 to 1000 N / 25 mm, and most preferably 100 to 1000 N / 25 mm.

[0128] The breaking strength when the metal material A and the metal material B are connected using the film is the tensile strength at break per 25 mm film width measured under the conditions described in the section of Examples.

[0129] 《Thin film manufacturing method》

[0130] The method for manufacturing the film containing the layer with thermoplastic resin as the main component is not particularly limited. For example, a resin composition can be obtained by heating a monomer or oligomer of a bifunctional epoxy compound to polymerize it, and a solvent is added to the obtained resin composition if necessary, and the film is obtained by coating it on a release film, curing, drying, and pressurizing it if necessary. In addition, the polymerization reaction can be carried out after coating on a release film, or after obtaining the film, and they can also be combined.

[0131] [Method of joining metal materials]

[0132] The method for manufacturing a connected body according to the present embodiment includes the steps of butting a cross section A of a flat metal material A against a cross section B of a flat metal material B, covering at least a portion of the facing portion with a film including a layer mainly composed of a thermoplastic resin, and melting and solidifying the film to connect the metal material A and the metal material B. The facing portion is a region spanning both the end edge A of the metal material A and the end edge B of the metal material B. By melting and solidifying the film, the film and the metal material A and the film and the metal material B are bonded, respectively, and the metal material A and the metal material B are connected.

[0133] The metal material and the film are the same as those constituting the above-mentioned connection body, and the description thereof will be omitted.

[0134] <Melting and Solidification of Film>

[0135] There is no particular limitation on the method of melting the film as long as the film can be heated and melted. Specifically, melting by at least one method selected from contact heating, warm air heating, hot pressing, pulse heater heating, hot plate welding, infrared heating, ultrasonic welding, vibration welding, and high-frequency induction welding can be cited. Among them, melting by pulse heater or hot pressing is preferred in terms of ease of manufacturing and process shortening.

[0136] In the case of hot pressing, heating and pressing are more preferably performed under the conditions of 100 to 400° C. and 0.001 to 20 MPaG.

[0137] The heating condition is more preferably 100 to 300° C., further preferably 120 to 250° C., and most preferably 150 to 220° C. By heating at 100 to 400° C., the film is efficiently deformed and melted, and effectively wets and spreads to the respective bonding surfaces of the film and the metal material A, and the film and the metal material B, thereby obtaining a high bonding strength.

[0138] The pressurization condition is preferably 0.001 to 20 MPaG, more preferably 0.005 to 10 MPaG, and most preferably 0.01 to 5 MPaG. By applying a pressurization of 0.001 to 20 MPaG, the film is efficiently deformed and wetted and spread effectively, thereby obtaining a high bonding strength.

[0139] By melting and solidifying the film, the film and the metal material A and the film and the metal material B are bonded to each other, and the metal material A and the metal material B are connected.

[0140] In the case of ultrasonic welding, the transmission frequency is preferably 10 to 70 kHz, more preferably 15 to 40 kHz.

[0141] From the viewpoint of adhesiveness and appearance, the ultrasonic wave application time is preferably 0.1 to 3 seconds, more preferably 0.2 to 2 seconds.

[0142] When applying pressure while applying ultrasonic waves, the pressure is preferably 0.01 to 20 MPaG, more preferably 0.1 to 10 MPaG, and even more preferably 0.2 to 5 MPaG. Within such a pressure range, the film deforms efficiently and wets and spreads effectively on the bonding surface, thereby obtaining high bonding strength.

[0143] In the case of high-frequency induction welding, the output power may be in the range of 100 to 5000 W, and the oscillation time may be adjusted according to the size and type of the resin substrate, and is preferably 1.0 to 10.0 seconds, and more preferably 1.5 to 8.0 seconds.

[0144] As a method for solidifying the molten film, there can be mentioned a method of natural cooling at room temperature or a method of natural cooling using a cooling device. It should be noted that "room temperature" refers to a normal room temperature in the range of 5 to 30° C. Among them, the method of natural cooling at room temperature is preferred from the perspective of ease of production.

[0145] In this specification, solidification means being solid at room temperature, that is, having no fluidity in a non-pressurized state at 23° C. However, the cured film may also have viscous properties.

[0146] Example

[0147] Next, specific examples of the present invention will be described, but the present invention is not specifically limited to these examples.

[0148] <Metal material A and metal material B>

[0149] As the metal material A and the metal material B, C1100 (tough pitch copper) having a width of 25 mm, a length of 100 mm, and a thickness of 0.1 mm was prepared.

[0150] <Weight Average Molecular Weight, Heat of Fusion and Epoxy Equivalent of Thermoplastic Epoxy Resins and Phenoxy Resins>

[0151] The weight average molecular weight, heat of fusion and epoxy equivalent of the thermoplastic epoxy resin and the phenoxy resin were respectively determined as follows.

[0152] (Weight average molecular weight)

[0153] A thermoplastic epoxy resin or a phenoxy resin was dissolved in tetrahydrofuran, and the measurement was performed under the following conditions using Prominence 501 (manufactured by Showa Kagaku K.K., Detector: Shodex (registered trademark) RI-501 (manufactured by Showa Denko K.K.)).

[0154] Column: LF-804 manufactured by Showa Denko K.K. × 2

[0155] Column temperature: 40°C

[0156] Sample: 0.4 mass% tetrahydrofuran solution of resin

[0157] Flow rate: 1ml / min

[0158] Eluent: Tetrahydrofuran

[0159] Calibration method: Conversion based on standard polystyrene

[0160] (Heat of Fusion)

[0161] 2 to 10 mg of a thermoplastic epoxy resin or phenoxy resin is weighed and placed in an aluminum pan, and the temperature is raised from 23°C to 200°C at 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. The heat of fusion is calculated from the area of ​​the endothermic peak during melting on the DSC curve and the weighed value.

[0162] (Epoxy Equivalent Weight)

[0163] The value was measured according to JIS K-7236: 2001 and converted into a value as a resin solid content. In the case of a simple mixture without reaction, it was calculated from the respective epoxy equivalents and contents.

[0164] <Example 1>

[0165] (Film P-1)

[0166] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction pipe and a thermometer, 1.0 equivalent (203 g) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 1.0 equivalent (12.5 g) of bisphenol S, 2.4 g of triphenylphosphine and 1,000 g of methyl ethyl ketone were added, and the temperature was raised to 100° C. while stirring under a nitrogen atmosphere. Dissolution was visually confirmed, and the mixture was cooled to 40° C. to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed therefrom to obtain a solid. A non-adhesive fluororesin film (Nitorfluon (registered trademark) No. 900UL, manufactured by Nitto Denko Corporation) is set on the upper and lower plates of the press, and the above-mentioned solid is arranged on the non-adhesive fluororesin film of the lower plate, and then the above-mentioned press is heated to 160°C, and the above-mentioned resin composition or phenoxy resin is heated and compressed for 2 hours to obtain a film-like solid adhesive (P-1) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight is about 37,000. The epoxy equivalent is above the detection limit (that is, there is almost no epoxy group). No melting heat peak was detected in DSC, confirming that it is amorphous.

[0167] (Connected Body)

[0168] The cross section A of metal material A is butted against the cross section B of metal material B, and the facing parts of the end edge A of metal material A and the end edge B of metal material B are covered with the above-mentioned film P-1 cut into a size of 20×25mm on the front side and the back side respectively across the width direction (25mm), and the metal materials are placed face down on a heating plate set at 200°C. A 3×3cm glass plate is placed on the film P-1 covering the above-mentioned facing parts, and a 2kg weight is placed on the glass plate for 1 minute to weld. After the above-mentioned welding, the above-mentioned glass plate and the weight are temporarily removed, and the above-mentioned film P-1 is cooled to room temperature. After cooling, a 3×3cm glass plate is placed on the film P-1 turned over to cover the facing parts on a heating plate set at 200°C again, and a 2kg weight is placed on the glass plate for 1 minute to weld, thereby producing a connection body.

[0169] <Example 2>

[0170] (Film P-2)

[0171] In a reaction apparatus with a stirrer, a reflux cooler, a gas introduction tube and a thermometer, 20 g of Fennotto (registered trademark) YP-50S (made by Nippon Steel Chemikar & Materia Co., Ltd., phenoxy resin, weight-average molecular weight of about 50,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60 ° C while stirring, and the dissolution was confirmed by visual inspection, and cooled to 40 ° C to obtain a resin composition having a solid content of 20% by mass. The above-mentioned resin composition was applied to a release film and dried at 120 ° C for 30 minutes to obtain a film P-2 having a solid content of 100% by mass and a thickness of 100 μm. The epoxy equivalent was above the detection limit (i.e., there was almost no epoxy group). No melting heat peak was detected in DSC, and it was confirmed to be amorphous.

[0172] (Connected Body)

[0173] A connected body was prepared in the same manner as in Example 1 except that P-2 was used as the membrane.

[0174] <Example 3>

[0175] (Film P-3)

[0176] In a reaction apparatus with a stirrer, a reflux cooler, a gas introduction tube and a thermometer, 20 g of Fennotto (registered trademark) YPS-007A (made by Nippon Steel Chemikar & Materia Co., Ltd., phenoxy resin, weight-average molecular weight of about 42,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60 ° C while stirring, and dissolved by visual confirmation, and cooled to 40 ° C to obtain a resin composition having a solid content of 20% by mass. The above-mentioned resin composition was applied to a release film and dried at 120 ° C for 30 minutes to obtain a film P-3 having a solid content of 100% by mass and a thickness of 100 μm. The epoxy equivalent was above the detection limit (i.e., almost no epoxy group). No melting heat peak was detected in DSC, and it was confirmed to be amorphous.

[0177] (Connected Body)

[0178] A connected body was prepared in the same manner as in Example 1 except that P-3 was used as the membrane.

[0179] <Example 4>

[0180] (Connected Body)

[0181] A connected body was produced in the same manner as in Example 1 except that a PET film (thickness 25 μm) was laminated on the solid adhesive P-1.

[0182] <Comparative Example 1>

[0183] (Connected Body)

[0184] The cross-section A of metal material A is butted against the cross-section B of metal material B, and the facing parts of the end edge A of metal material A and the end edge B of metal material B are covered and sealed with an adhesive tape (セキスイセロテープ(registered trademark) No.252, manufactured by Sekisui Chemical Co., Ltd., with a thickness of 50 μm before manufacturing the connected body) cut into a size of 20×25 mm on the front side and the back side respectively across the width direction (25 mm) to manufacture a connected body.

[0185] <Comparative Example 2>

[0186] (Connected Body)

[0187] A connected body was produced in the same manner as in Example 1 except that a crystalline olefin hot melt adhesive film (Elufan (registered trademark) NT-120, manufactured by Nippon Matai Co., Ltd., thickness before forming a connected body was 80 μm) was used as the film and the temperature of the hot plate was set to 150° C. The melting heat peak in DSC was 60 J / g.

[0188] <Comparative Example 3>

[0189] (Connected Body)

[0190] A connected body was produced in the same manner as in Comparative Example 1 except that a heat-resistant adhesive tape (polyimide tape, PB416-20-30, manufactured by Azwan Co., Ltd.) cut into a size of 20×25 mm was used as the adhesive tape.

[0191] [Breaking strength measurement_Tensile test]

[0192] The tensile strength of the connected bodies obtained in Examples 1 to 4 and Comparative Examples 1 to 3 was measured. The measurement conditions were as follows: a universal testing machine Autograph AG-X Plus manufactured by Shimadzu Corporation was used, the chuck distance was set to 13 cm, and the tensile speed was set to 5 mm / min. The measurement results (breaking strength) are shown in Table 1.

[0193] The measurements were performed under the conditions of "normal temperature: 23°C", "high temperature of 80°C", and "immersion in ethylene glycol". In Table 1, the values ​​measured under the "high temperature of 80°C" condition are the values ​​obtained by measuring in an atmosphere of 80°C. In Table 1, the values ​​measured under the "immersion in ethylene glycol" condition are the values ​​obtained by taking out the sample after immersion in ethylene glycol at 40°C for 5 days, immersing it in water for 5 seconds, wiping off the ethylene glycol, photographing the appearance, and then leaving it to stand for 20 to 30 minutes before measuring it at normal temperature.

[0194] [Production line contamination]

[0195] After the tensile test, observe whether the adhesive surface is exposed on the surface. If the adhesive surface is exposed on the surface, it may contaminate the production line. Therefore, the situation where the adhesive surface is exposed is evaluated as "×", and the situation where the adhesive surface is not exposed is evaluated as "0". The evaluation results are shown in Table 1.

[0196]

[0197] Industrial Applicability

[0198] The present invention is suitable for applications such as connecting frame materials in a production line for LED lead frames and connecting substrate materials in a production line for flexible printed substrates, but is not particularly limited to these exemplified applications.

[0199] Explanation of symbols

[0200] 1Metal material A

[0201] 2Metal Material B

[0202] 3. Membrane (membrane constituting the connecting body)

[0203] 4 docking surface

[0204] 5. Section A

[0205] 6 Section B

[0206] 7 End edge A

[0207] 8 End edge B

[0208] 9 Opposite parts

Claims

1. A connection body of metal materials, which is formed by butting a cross section A of a flat metal material A with a cross section B of a flat metal material B, and connecting the metal material A and the metal material B by covering at least a portion of the facing portion with a film containing a layer mainly composed of a thermoplastic resin, wherein the facing portion is a region spanning both an end edge portion A of the metal material A and an end edge portion B of the metal material B, wherein: The film is a film that has undergone melting and solidification at the facing portions. 2 . The connection body of metal materials according to claim 1 , wherein the metal material A and the metal material B are at least one selected from a metal plate having a thickness of 1 mm or less and a metal foil having a thickness of 1 mm or less. 3 . The connection body of metal materials according to claim 1 , wherein the metal material A and the metal material B are in a strip shape, and the metal material A and the metal material B are butted together so as to be continuous in a length direction. 4 . The metal material connection body according to claim 3 , wherein the metal material A and the metal material B are coiled materials formed by winding at least one selected from a metal plate and a metal foil into a coil shape.

5. The connection body of metal materials according to claim 1 is formed by coating two planar portions, namely, a planar portion on the front side of the metal material A and the metal material B and a planar portion on the back side of the metal material A and the metal material B. The metal material connection body according to claim 1 , wherein the thermoplastic resin is an amorphous thermoplastic resin. 7 . The metal material connection body according to claim 6 , wherein the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resins and phenoxy resins. 8 . The metal material connection body according to claim 7 , wherein the amorphous thermoplastic resin is an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, or an amorphous thermoplastic resin containing no epoxy group. 9 . The metal material connection body according to claim 1 , wherein the film has a thickness of 10 μm to 3 mm. 10 . The metal material connection body according to claim 1 , wherein the film has an adhesive on a surface covering the facing portion, and the adhesive serves to temporarily fix the film and does not serve as an adhesive function.

11. A method for connecting metal materials, wherein a cross-section A of a flat metal material A is butted against a cross-section B of a flat metal material B, at least a portion of the facing portions of a region spanning an end edge A of the metal material A and an end edge B of the metal material B is coated with a film comprising a layer mainly composed of a thermoplastic resin, and the film is melted and solidified to connect the metal material A to the metal material B.

Citation Information

Patent Citations

  • Coil material connection method and device

    JP2012061511A